2010
DOI: 10.1021/la904576z
|View full text |Cite
|
Sign up to set email alerts
|

Reaction Pathways of 2-Iodoacetic Acid on Cu(100): Coverage-Dependent Competition between C−I Bond Scission and COOH Deprotonation and Identification of Surface Intermediates

Abstract: The chemistry of 2-iodoacetic acid on Cu(100) has been studied by a combination of reflection-absorption infrared spectroscopy (RAIRS), X-ray photoelectron spectroscopy (XPS), temperature-programmed reaction/desorption (TPR/D), and theoretical calculations based on density functional theory for the optimized intermediate structures. In the thermal decomposition of ICH(2)COOH on Cu(100) with a coverage less than a half monolayer, three surface intermediates, CH(2)COO, CH(3)COO, and CCOH, are generated and chara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 17 publications
1
6
0
Order By: Relevance
“…The O 1s spectrum can be fitted with three peaks located at 531.3, 532.7, and 533.7 eV. Previously, the respective O 1s binding energies have been found at 532.4 eV (broad) and 532.9 eV for the acetic acid on Cu(110) and the iodoacetic acid on Cu(100). , Upon deprotonating the acetic acid on Cu(110) to form acetate, the O 1s peak is shifted to 531.6 eV . Acetate on hydroxylated NiO(111) has an O 1s binding energy of 531.2 eV .…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…The O 1s spectrum can be fitted with three peaks located at 531.3, 532.7, and 533.7 eV. Previously, the respective O 1s binding energies have been found at 532.4 eV (broad) and 532.9 eV for the acetic acid on Cu(110) and the iodoacetic acid on Cu(100). , Upon deprotonating the acetic acid on Cu(110) to form acetate, the O 1s peak is shifted to 531.6 eV . Acetate on hydroxylated NiO(111) has an O 1s binding energy of 531.2 eV .…”
Section: Resultsmentioning
confidence: 91%
“…Previously, the respective O 1s binding energies have been found at 532.4 eV (broad) and 532.9 eV for the acetic acid on Cu(110) and the iodoacetic acid on Cu(100). 11,12 Upon deprotonating the eV has been reported for H 2 O on Cu(100) and Ni(110). 14,15 Four deconvoluted peaks are obtained at 284.9, 286.2, 287.8, and 289.7 eV after curve-fitting to the C 1s spectrum (Figure 2).…”
Section: ■ Results and Discussionmentioning
confidence: 98%
“…No ICH 2 CN desorption below 1.2 L indicates that ICH 2 CN dissociates on the surface at 180 K or during the heating course in the TPD experiment. The previous studies regarding the chemistry of alkyl iodides on copper single crystals indicated that C−I bond scission is the primary reaction step, which occurs below 180 K, resulting in the formation of adsorbed iodine atoms and alkyl groups.29−31 Indeed, the separate X-ray photoelectron spectroscopic study of ICH 2 CN/Cu(100), as shown in supporting FigureS1, confirms the C−I breakage at 180 K. FigureS1shows the I 4d XP spectra taken after ICH 2 CN adsorption (2.0 L) on Cu(100) at 180 K, followed by annealing to 210 K. There are four resolved peaks in the 180 K spectrum that can be attributed to ICH 2 CN molecules (50.8 and 52.5 eV) and iodine atoms (49.5 and 51.2 eV) on Cu(100) 32,33. The C−I bonds dissociate completely at 210 K.Spectroscopic Evidence of Coverage-Dependent CH 2 CN Adsorption Structures.…”
mentioning
confidence: 99%
“…In the 370 K spectrum, the peaks of I 4d3/2 at 51.3 eV and I 4d5/2 at 49.6 eV are ascribed to I adsorbed on Cu(100) in accordance with previously reported assignments. 19 This result, together with the absence of other iodine signals, also indicates that both CÀI bonds in 1,3-C 6 H 4 I 2 have dissociated on Cu(100) at 370 K, leaving atomic iodine on the surface. The 230, 290, and 320 K spectra can be nicely fitted with four peaks.…”
Section: ' Results and Discussionmentioning
confidence: 88%
“…However, none of hydrocarbons was detected, but H 2 . In Figure 5 showing the TPR/D spectra of hydrogen, it is found that H 2 starts to desorb at approximately 550 K and extends up to ∼900 K. This result suggests that no H atoms are present on the surface before 550 K, i.e., the CÀH bonds remaining intact before 550 K, because it has been known that recombination of H atoms on Cu(100), forming H 2 , occurs around 300 K. 19 After considering that the two CÀI bonds of 1,3-C 6 H 4 I 2 have dissociated at 370 K, as shown in Figure 2, C 6 H 4 is suggested to be the species present on the surface at this temperature. In the inset of Figure 5, the yield of H 2 desorption increases linearly with exposure of 1,3-C 6 H 4 I 2 and levels off as the exposure is approximately above 3.0 L. Figure 6 shows the Auger electron spectra obtained after adsorption of 3 L 1,3-C 6 H 4 I 2 on Cu(100) at 180 K, followed by briefly heating the surface to 450 and 980 K. Both the carbon (∼276 eV) and iodine (∼512 and 521 eV) peaks are detected at 450 K. The carbon is ascribed to the presence of C 6 H 4 from CÀI bond breakage of 1,3-C 6 H 4 I 2 .…”
Section: ' Results and Discussionmentioning
confidence: 96%